2011
DOI: 10.1111/j.1365-313x.2011.04546.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy differentially controls plant basal immunity to biotrophic and necrotrophic pathogens

Abstract: SUMMARYIn plants, autophagy has been assigned 'pro-death' and 'pro-survival' roles in controlling programmed cell death associated with microbial effector-triggered immunity. The role of autophagy in basal immunity to virulent pathogens has not been addressed systematically, however. Using several autophagy-deficient (atg) genotypes, we determined the function of autophagy in basal plant immunity. Arabidopsis mutants lacking ATG5, ATG10 and ATG18a develop spreading necrosis upon infection with the necrotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
199
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(215 citation statements)
references
References 67 publications
11
199
2
3
Order By: Relevance
“…MDC-labeled structures were absent, which was coupled with increased fungal growth ( Figures 7A to 7C). In accordance, previous reports (Lai et al, 2011;Lenz et al, 2011) have also linked autophagy mutants (i.e., atg18) to enhanced susceptibility to B. cinerea. Taken together, these results indicate that B. cinerea challenge triggers the formation of MDC-labeled autophagosomal structures in Arabidopsis plants during the resistant response, and when this response is blocked, susceptibility ensues.…”
Section: Bag6 Processing Triggers Autophagy In Arabidopsissupporting
confidence: 73%
See 3 more Smart Citations
“…MDC-labeled structures were absent, which was coupled with increased fungal growth ( Figures 7A to 7C). In accordance, previous reports (Lai et al, 2011;Lenz et al, 2011) have also linked autophagy mutants (i.e., atg18) to enhanced susceptibility to B. cinerea. Taken together, these results indicate that B. cinerea challenge triggers the formation of MDC-labeled autophagosomal structures in Arabidopsis plants during the resistant response, and when this response is blocked, susceptibility ensues.…”
Section: Bag6 Processing Triggers Autophagy In Arabidopsissupporting
confidence: 73%
“…In accordance, we show that BAG6 processing triggers autophagy and inhibits B. cinerea pathogenic development. When autophagy is inhibited chemically or genetically, a marked increase in susceptibility to B. cinerea is observed (Lai et al, 2011;Lenz et al, 2011). Finally, using transient assays with the cleaved BAG6 followed by TEM, we provide clear evidence for autophagic structures during this immune response.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Arabidopsis ATG7 knockout mutants and ATG6 RNAi plants reportedly support the increased growth of the virulent hemibiotrophic pathogen Pst DC3000 (Patel and Dinesh-Kumar, 2008;Hofius et al, 2009). However, these observations obviously contradict the recent report that three Arabidopsis mutant lines, Atatg5, atg10, and atg18a, showed an enhanced resistance towards the same virulent pathogen Pst DC3000 (Lenz et al, 2011). Lenz et al reported that these atg plants have a higher level of SA and an increased SA-dependent gene expression, indicating that autophagy negatively regulates SA-dependent immunity resistance to the hemibiotrophic pathogen Pst DC3000 (Lenz et al, 2011).…”
Section: Role Of Autophagy In Plant Responses To the Compatible Pathocontrasting
confidence: 54%